Perceptions of Conflict between Self-Efficacy, Job Satisfaction, and Work-Life Balance among University Teachers - Khadka, Ajaya Kumar; Khadka, Srijana (Nepal Journal of Multidisciplinary Research, 2023)
The study explored the relationship between work-life balance, perceptions of personal conflict between work and family, university teachers' self-efficacy, and job satisfaction. The study used 210 responses from university teachers working in different public and private colleges in Kathmandu Metropolitan City, the capital city of Nepal, based on a purposive sampling technique. The data were analyzed using regression and correlation analysis. Findings showed a good correlation between self-efficacy, job satisfaction, perceived work-family conflicts, and perceived balance of teachers' work life. In addition, the findings discovered that conflict between work and family was the most significant predictor of job satisfaction. The results indicate that increasing teachers' sense of self-efficacy, fostering a better work-life balance, and decreasing work-family conflict can all benefit teachers' contentment with their jobs and their likelihood of staying in them. These results have considerable ramifications for schools, governments, and other educational stakeholders looking to boost educator satisfaction and happiness on the job.